Pengaruh Good Corporate Governance, Financial Distress Dan Ukuran Perusahaan Terhadap Manajemen Laba - Hadi Sucipto; Umi Zulfa (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
This study aims to determine the effect of Good Corporate Governance, Financial Distress and Company Size on earnings management calculated using discretionary accruals. This type of research is a quantitative description research. This research uses purposive sampling method as a method of selecting samples. The population in this study were all 10 pharmaceutical companies listed on the Indonesia Stock Exchange (BEI). Based on predetermined criteria, there are 7 companies with an observation period of 5 years from 2015-2019. Hypothesis testing in this study uses multiple regression analysis techniques. The results of this study indicate that Good Corporate Governance has no significant effect on earnings management, financial distress has no significant effect on earnings management and firm size has no significant effect on earnings management.